2015
DOI: 10.1515/hukin-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

The Gluteus Medius Vs. Thigh Muscles Strength Ratio and Their Relation to Electromyography Amplitude During a Farmer’s Walk Exercise

Abstract: The strength ratio between hamstrings and quadriceps (H/Q) is associated with knee injuries as well as hip abductor muscle (HAB) weakness. Sixteen resistance trained men (age, 32.5 ± 4.2 years) performed 5 s maximal isometric contractions at 75° of knee flexion/extension and 15° of hip abduction on a dynamometer. After this isometric test they performed a Farmer’s walk exercise to find out if the muscle strength ratio predicted the electromyography amplitude expressed as a percentage of maximum voluntary isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The H/Q FUNC ratio at this velocity indicates the maximum possibility of the hamstrings breaking function, and is used for the co-activation of the flexors and extensors estimation ( Aagaard et al, 1998 ). The value of the H/Q FUNC ratio is influenced by the joint angle, individual differences in muscle fibres distribution, sport type specifics ( Aagaard et al, 1998 ; Coombs and Garbutt, 2002 ) and a hip abductor strength ratio ( Stastny et al, 2015a ; Stastny et al, 2015b ). It has been suggested that the H/Q FUNC ratio in a range of 0.7–1.0 is an indicator of adequate joint stability ( Aagaard et al, 1998 ; Ayala et al, 2012 ; Dauty et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…The H/Q FUNC ratio at this velocity indicates the maximum possibility of the hamstrings breaking function, and is used for the co-activation of the flexors and extensors estimation ( Aagaard et al, 1998 ). The value of the H/Q FUNC ratio is influenced by the joint angle, individual differences in muscle fibres distribution, sport type specifics ( Aagaard et al, 1998 ; Coombs and Garbutt, 2002 ) and a hip abductor strength ratio ( Stastny et al, 2015a ; Stastny et al, 2015b ). It has been suggested that the H/Q FUNC ratio in a range of 0.7–1.0 is an indicator of adequate joint stability ( Aagaard et al, 1998 ; Ayala et al, 2012 ; Dauty et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that variations in the strength ratio between muscle groups can affect muscle activity during an exercise. For example, if HAB strength is greater than knee flexion strength, Gmed activity during the Farmer's walk exercise (walking while carrying dumbbells in the hands at the side of the body) is greater than if knee flexion is stronger than HAB ( 43 ). Similarly, it has been shown that during split squats and walking lunges, EMG activity of the quadriceps and hamstrings can differ depending on HAB and knee flexion strength.…”
Section: G Med Activity Estimationmentioning
confidence: 99%
“…This article does not take into account that the Gmed can be anatomically subdivided into 3 parts, all of which can experience different levels of activity depending on exercise selection ( 32 ). Additionally, Gmed activation can vary as a consequence of different strength ratios of the Gmed to the quadriceps or hamstrings ( 43 , 45 ); altering the exercise intensity ( 44 ); changing the kinematics ( 10 ); changing the way the eccentric actions are performed ( 21 ); training experience ( 8 , 17 , 27 ); and asymmetrical loading ( 44 ). Another issue, which has not been included in this article, is the activity ratio between Gmed and the tensor fasciae latae.…”
Section: Limitationsmentioning
confidence: 99%
“…Other strength deficiencies might be found in conventional hamstring : quadriceps (H/Q) ratios of 0.5 to 0.6 (Aagaard, Simonsen, Magnusson, Larsson, & Dyhre-Poulsen, 1998), which can increase along with tested speed up to the optimal ratio 1:1. The HAB, quadriceps (Q) and hamstrings (H) reciprocal strength ratio has been shown as possible predictor of electromyography (EMG) amplitude during load carrying walking (Stastny et al, 2015) at moderate intensity. The results of this study suggest that a HAB/H ratio with a critical value of 1 influences the level of muscle bioelectrical activity of the Gmed and ratio of 0.5 might be used to separate the muscle activity by H/Q or HAB/Q ratios.…”
Section: Introductionmentioning
confidence: 99%